Illuminating the geology: Post-injection reservoir characterisation of the CO2CRC Otway site. (July 2019) - Dance, Tess; LaForce, Tara; Glubokovskikh, Stanislav; Ennis-King, Jonathan; Pevzner, Roman
Highlights: Using integrated monitoring data, we have reviewed the structural and stratigraphic features at a CO2 storage site. We discovered minor faults which were unrevealed before CO2 injection. Plausible conclusions about reservoir heterogeneity are drawn from observations. Static and dynamic models are improved by updating permeability distribution with history matching of pressure data. Findings are very informative as a case study for others contemplating reservoir management of a CO2 storage site. Abstract: Proper site characterisation is vital in the planning stages of a CO2 storage project; but we can also learn a good deal about the reservoir once the injection is underway or has been completed. During CO2CRC Otway Project Stage 2C, sources of valuable information about storage performance have been generated as a consequence of the staged injection of 15, 000 t of CO2 rich gas, as well as observations from time-lapse seismic surveys and well monitoring data. Now that injection has ceased for Stage 2C, the geological model is compared against field observations for the period spanning injection and 23 months after injection ended. The post-injection reservoir characterisation has proven important to refine the static and dynamic models for future field development and added assurance about the long-term stabilisation of the CO2 plume. The south-eastern progress of plume development, as seen on the time-lapse seismic data, has led to a review of the structural interpretation and horizon-fault geometry represented in the models. The developing plume has illuminated the extent of splay faults previously unresolved on the baseline seismic data. Saturation profiles interpreted from pulsed-neutron logs at the injection and observation wells show a preference for higher saturations occurring in high permeability distributary channels penetrated by each of the wells. This has reduced the uncertainty in predicting connectivity of this facies between the wells. The pressure data from numerous injection events has been used to refine the characterisation of the average horizontal permeability of the reservoir zone, and the vertical permeability of the intra-formational seal. It has also been used to infer near-field bounding conditions of the interior splay fault, which in turn improves our understanding of containment at the site.